Determinants of Austrian international trade: Analysis based on the gravity model - Lucie Davidová; Vladimír Benáček (Charles University in Prague, Institute of Economic Studies (IES), 2014)
The purpose of this paper is to examine Austrian foreign trade and estimate the country's export function. The analysis is based on the gravity model of trade in the log-log form, augmented by additional variables in order to control for the impact of institutions on decision-making. Our panel dataset consists of 3,396 observations of Austrian exports to 211 countries over the period from 1995 to 2011. At that time, the Austrian export was very closely dependant on the German market, which the model proved to be a natural outcome. In other respects it has been, however, diversified among many smaller trade partners whose importance has been gradually shifting eastwards. We employ Fixed Effects and Random Effects as estimation techniques. By taking advantage of the panel data structure, we estimate the gravity equation as two alternative one-way estimators - as 17 segments of cross-sections and as 211 time series. This allows us to estimate factors related to two complementary questions of "where to export" and "how much to export over time". For each question we test and quantify the relevance of nine economic and ten institutional factors.
Keywords: C13; C23; F10; F12; F14; 330; Austria; export; gravity model; fixed effects; random effects